Generating quasigroups for cryptographic applications - Kościelny, Czesław (Zielona Góra: Uniwersytet Zielonogórski)
A method of generating a practically unlimited number of quasigroups of a (theoretically) arbitrary order using the computer algebra system Maple 7 is presented. This problem is crucial to cryptography and its solution permits to implement practical quasigroup-based endomorphic cryptosystems.
Keywords: quasigroups; latin squares; stream-ciphers; cryptography